European judicial systems as a challenge for democracy (Antwerpen, 2015)
"The role of the European judiciary in the process of European integration cannot be overestimated. European integration after the second world war is usually analyzed from the perspective of political decisions. However, in the public debate we very often forget how much we owe to the Court of Justice of the European Union and the European Court of Human Rights."